Enhancing CP measurement of the Yukawa interactions of top-quark at e−e+ collider - Ma, Kai (Physics letters. B, 2019)
It is well known that CP-violating coupling of the Yukawa interaction of top-quark is a promising candidate of a new source of CP violation effect. Precisely measurement of its CP properties is crucial for understanding new physics above the electroweak scale. In this paper, we introduce a complete analysis method for probing CP violation effects in the associated production of top-quark pair and Higgs boson at e−e+ collider. Reconstructions of the top-quarks are not needed in our strategy. The observables are defined based on spin correlation effects of the leptons emerging from decays of top-quarks, and their formal expressions are universal at any reference frames. Two reference frames, the rest frame of the top-quark pair and the rest frame of Higgs boson, are examined. Importantly, large enhancement effects for both CP-odd and CP-even observables are observed in the rest frame of Higgs boson. This can be essential for probing CP violation effects at future e−e+ collider.